Application Fuzzy For Measuring Lecturer Performance Using Matlab Software - Alwendi; Mandopa, Andi Saputa (EDUPEDIA Publisher, 2023)
Research by Lecturer, Graha University Nusantara Padangsidimpuan, Simrittabumas Data still in Guidance Category for Upgrade to Intermediate Category are required to apply. For this, we need an application that can calculate and document the lecturer's performance in the resulting research. The purpose of this study is to apply fuzzy logic with Mamdani method to evaluate the research achievements of lecturers at Graha Nusantara Padangsidimpuan University. This study uses Mamdani fuzzy logic. The fuzzy Mamdani method is a method of mapping the input space to the output space. This method is a mathematical framework for expressing uncertainty, ambiguity, inaccuracy, lack of information, and partial truth. The phase of research using the Mamdani method is to create input variables from Sinta-accredited papers, Simlitabmas Grant papers, and papers from international and national journals. Find the maximum and minimum values for each variable. Create a fuzzy set using the Mamdani method. Building assertions with defuzzification using Matlab.